Different processes contributing to the development of preferred oriented platinum surfaces by fast periodic potential perturbation techniques - Perdriel, Carlos L. (1986)
The development of preferred oriented (po) platinum surfaces, either [(100)poPt] or [(111)poPt], in acid solutions results from the contributions of electroadsorption/electrodesorption processes and electrodissolution/electrodeposition of platinum. In the case of [(100)poPt], the overall reaction implies no appreciable roughening, whereas for [(111)poPt] the voltammetric charge increases slightly after the preferred orientation treatment. Runs were made with periodic potential scans, either triangular or rectangular, under conditions corresponding to the optimal conditions for development of the [(100)poPt] and [(111)poPt] surfaces. The amount of net soluble platinum as determined by chemical analysis increases linearly with the duration of the periodic potential perturbation applied to the platinum polycrystalline electrode. The net amount of dissolved platinum produced at perturbation frequencies required for the development of the preferred orientation is nearly two orders of magnitudes smaller than that found under conventional triangular potential voltammetry. The results offer the possibility of interpreting the electrochemical faceting of platinum electrodes in acid electrolytes.